Vitellogenin and Vitellogenin-Like Genes in the Brown Planthopper - Shen, Yan; Chen, Yuan-Zhi; Lou, Yi-Han; Zhang, Chuan-Xi (Frontiers in Physiology, 2019)
Vitellogenin (Vg) is precursor of vitellin. Here, we identiﬁed a Vg (NlVg) and two Vg-likes (NlVg-like1 and NlVg-like2) from the brown planthopper, Nilaparvata lugens. Phylogenetic analyses showed that NlVg-like1 and NlVg-like2 are not clustered within the conventional insect Vgs involved in vitellogenesis. Temporo-spatial expression analysis showed that NlVg and NlVg-like2 transcript levels increased significantly 24 h after emergence and mainly expressed in female adults. However, NlVg-like1 was expressed during all stages and both genders. Tissue-specific analysis showed that all three genes were most highly expressed in the fat body. The injection of double-stranded RNA targeting NlVg showed that NlVg is essential not only for oocyte development, but also nymph development. Knockdown of NlVg-like1 in female adults resulted 18% of offspring embryos failing to hatch and dying before leaving the eggshell, suggesting that it plays an important role in late embryogenesis. About 65% of eggs laid by females treated with double-stranded RNA targeting NlVg-like2 could not hatch, indicating its role in nutrition absorption for oocyte or embryonic development. Our results illustrate the structural and functional differences of the Vg and Vg-like genes and provide potential targets for insect pest management based on RNA interference.